Physical characterization of a glucoamylase gene (STA2) from Saccharomyces diastaticus - Lambrechts, Marius George,1965- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1990.